Hubungan Citra Tubuh dengan Kepercayaan Diri pada Remaja Putri di SMP Negeri 1 Kediri Tabanan : Penelitian - Ni Kadek Nita Lestari; Ni Putu Dita Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Adolescents face problems related to imperfect body shape, which is related to physical changes that do not align with their expectations. They believe that the ideal standard should match the characteristics of idols on social media. This often triggers negative perceptions of body image, lowers self-esteem, and leads to social isolation and difficulty adapting. The purpose of this study is to examine the correlation between body image and self-esteem in adolescent girls at SMP Negeri 1Kediri Tabanan. This quantitative research uses a correlational research type and a cross-sectional approach. The sample was taken using a non-probability sampling technique, specifically total sampling, with 117 adolescent girls as participants. The data were analyzed using the Spearman Rank test to measure the strength of the correlation between two categorical variables using an ordinal scale. The results showed a coefficient of α=0.05 with a p-value of 0.001, meaning the p-value < α (α=0.05), which indicates that the alternative hypothesis (Ha) is accepted. The Correlation Coefficient value is 0.296, which indicates a weak correlation. Therefore, it can be concluded that there is a weak relationship between body image and self-esteem in adolescent girls at SMP Negeri 1 Kediri Tabanan. It is hoped that this study will provide insights to adolescent girls about the importance of a positive body image and high self-esteem.